Deciphering the role of the conjugate's phycoerythrin label in complement‐mediated interference occurring in HLA single antigen Luminex bead assays. (15th April 2022) - Devriese, Magali; Hays, Constantin; Jouffrey, Julie; Usureau, Cédric; Carmagnat, Maryvonnick; Caillat‐Zucman, Sophie; Taupin, Jean Luc
Abstract : Complement‐mediated interference is a well described phenomenon in single antigen bead (SAB) Luminex assay that leads to falsely low or negative results for anti‐HLA antibody (Ab). In a context of high amount of Ab, the enrichment of the Ab around the bead can lead to complement cascade activation and deposition, thereafter impairing Ab detection. EDTA is now routinely used to circumvent this interference. In this report, we attempted to decipher the role of the phycoerythrin (PE) label conjugated to the secondary Ab in this interference. Indeed, PE is a huge molecule (240 kDa) that could participate to limiting access of the conjugate to its Ab target on the bead. To this purpose, 22 sera displaying complement interference without pre‐treatment with EDTA were compared on SAB assay with three detection strategies: the recommended PE‐conjugated secondary Ab (IgGPE), an Alexa Fluor 532‐conjugated Ab (IgGAF) bearing a tiny 724 Da fluorochrome, and a biotinylated Ab followed by PE‐conjugated streptavidin (IgGBiot). Complement interference occurred with the three detection methods, but its depth, defined by the percentage of MFI loss with neat serum, was the highest for IgGPE. Our study highlighted the partial role of the PE fluorochrome in complement interference in SAB assays.